Conformational and Stereodynamic Behavior of Five to Seven-membered 1-Aryl-2-iminoazacycloalkanes - Díaz, Jimena Estela (2019)
The stereodynamic behavior of 1-arylpyrrolidin-2-imines, having a C aryl -N stereogenic axis, has been studied by means of dynamic nuclear magnetic resonance and density functional theory calculations, evaluating the steric effect of ortho-aryl substituents. The rotational barrier due to E/Z isomerism about the C=N-H bond was also determined. The dynamic stereochemistry of homologous six- and seven-membered iminoazacycloalkane rings and their oxo-analogues was also comparatively investigated, evidencing a ring size effect. It was found that the seven-membered heterocycle shows additional dynamic features because of ring inversion.